The Prevalence of Irritable Bowel Syndrome Using Rome IV Criteria in Medical Student and The Related Factors - Ahani, Ardhi Rahman; Syam, Ari Fahrial; Putranto, Rudi; Nugroho, Pringgodigdo (Jurnal Penyakit Dalam Indonesia, 2022)
Introduction. Medicine is a long study time. Medical student will take five years study to accomplish the education. Because the lot of task and some taken test, some medical student will face irritable bowel syndrome in their study periods. This study aims to identify the prevalence of IBS in medical student and related factors.Methods. A cross-sectional study of 350 medical student Universitas Indonesia from first grade until fifth grade was done during November-December 2016. This study used stratified randomized sampling. The Rome IV criteria was used for diagnosing IBS. Interview with questionnaire guided was applied to all subjects. A bivariate analysis was done to know relationship between IBS and its related factors using chi-square, unpaired t-test, and their alternatives. Multivariate analysis was done using logistic regression test.Results. The IBS proportions were 18.3% in the female medical students and 9.7% in the male medical students (95% CI 1.11- 3.91). The highest subtype was diarrhea subtype (53.1%). Both student-life stress inventory score (stressor and response to stressor) were higher in IBS group than in non-IBS group (For stressor (66.4 (SB 11.4) vs 60.0 (SB 12.2), p=0,001) and for responseto stressor (64.0 (41-97) vs 55,0 (35-88), p<0,0001). Female sex and anxiety were related to IBS ((aOR 2.14; 95% CI 1.12-4.08) and (aOR 2.89; 95% CI 1.43-5.83)).Conclusions. The IBS proportions were 18.3% in the female medical students and 9.7% in the male medical students (95% CI 1.11- 3.91) with predominant diarrhea subtype (53.1%). Anxiety and woman were related to IBS.